2019
DOI: 10.7306/gq.1494
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and geochemical studies of secondary mineral assemblages related to deterioration of building materials

Abstract: and Tech nol ogy, Fac ulty of Ge ol ogy, Geo phys ics and En vi ron men tal Pro tec tion, al. A. Mickiewicza 30, 30-059 Kraków, Po landMarsza³ek, M., Dudek, K., Gawe³, A., Czerny, J., 2019. Min er al og i cal and geo chem i cal stud ies of sec ond ary min eral as semblages re lated to de te ri o ra tion of build ing ma te ri als. Geo log i cal Quar terly, 63 (4): 683-698, doi: 10.7306/gq.1494The study was aimed at min er al og i cal and geo chem i cal char ac ter is tics of sec ond ary phases re lated to de te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Minerals 2020, 10, x FOR PEER REVIEW 3 of 19 rusticated Pińczów limestone, but any detailed information about the other elevation materials was not encountered. In the course of our previous research [20], we observed that the stony elements below the rusticated blocks of the Pińczów limestone were also covered with a thin layer of a beige-brown, highly exfoliated cement render. However, some of the limestone blocks in the row of the façade below the small shaft contained replacements and thick, bright render of a different nature than the previous.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Minerals 2020, 10, x FOR PEER REVIEW 3 of 19 rusticated Pińczów limestone, but any detailed information about the other elevation materials was not encountered. In the course of our previous research [20], we observed that the stony elements below the rusticated blocks of the Pińczów limestone were also covered with a thin layer of a beige-brown, highly exfoliated cement render. However, some of the limestone blocks in the row of the façade below the small shaft contained replacements and thick, bright render of a different nature than the previous.…”
Section: Introductionmentioning
confidence: 84%
“…The latter will then first precipitate darapskite and, in the end, nitratine. Nitrate salts-nitratine NaNO 3 and nitre KNO 3 -have been detected on the surface of the Jurassic limestone in the vicinity of the efflorescence [20]. Aphthitalite (K,Na)3Na(SO4)2, in EDS analyses revealing the presence of Na, K, S and O, occurs in the form of anhedral, often isometric crystals and irregular aggregates, as shown in Figure 11c.…”
Section: Cement Mortar Between Stony Blocks Of the Subwall Below The Pavement Levelmentioning
confidence: 93%
See 2 more Smart Citations
“…It is found in the sodium sulphate deposits in the Northern Great Plains of Canada, on the surface of playa lakes in Central and Northeast Spain and on the dry shores of the Aral Sea (Valero-Garcés et al 2000;Kelley and Holmden 2001;Crétaux et al 2009;Cabestrero et al 2018). However, the crystallisation of mirabilite due to the moisture present in the pores in masonry is regarded as a harmful process resulting from salt precipitation on building materials (Ruiz-Agudo et al 2007;Marszałek et al 2019). It has been identified that the precipitation of mirabilite and other similar salts is provoked by the freezing processes that occur in the glacial or subglacial bodies of water in Antarctica (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%